Dynamics of Nigral Iron Accumulation in Parkinson's Disease: From Diagnosis to Late Stage. Issue 8 (25th May 2022) - Du, Guangwei; Wang, Ernest; Sica, Christopher; Chen, Hairong; De Jesus, Sol; Lewis, Mechelle M.; Kong, Lan; Connor, James; Mailman, Richard B.; Huang, Xuemei
Abstract: Background: Higher nigral iron has been reported in Parkinson's disease (PD). Objective: The aim is to understand the dynamics of nigral iron accumulation in PD and its association with drug treatment. Methods: Susceptibility magnetic resonance imaging data were obtained from 79 controls and 18 drug‐naive (PDDN ) and 87 drug‐treated (PDDT ) PD patients. Regional brain iron in basal ganglia and cerebellar structures was estimated using quantitative susceptibility mapping. Nigral iron was compared between PDDN and PDDT subgroups defined by disease duration (early [PDE, <2 years], middle [PDM, 2–6 years], and later [PDL, >6 years]). Associations with both disease duration and types of antiparkinson drugs were explored using regression analysis. Results: Compared to controls, PDDN had lower iron in the substantia nigra ( P = 0.018), caudate nucleus ( P = 0.038), and globus pallidus ( P = 0.01) but not in the putamen or red nucleus. In contrast, PDDT had higher iron in the nigra ( P < 0.001) but not in other regions, compared to either controls or PDDN . Iron in the nigra increased with disease duration (PDE > PDDN [ P = 0.001], PDM > PDE [ P = 0.045]) except for PDM versus PDL ( P = 0.226). Levodopa usage was associated with higher ( P = 0.013) nigral iron, whereas lower nigral iron was correlated with selegiline usage ( P = 0.030). Conclusion: Nigral iron is lower before the start of dopaminergic medication and then increases throughout the disease until it plateaus at late stages, suggesting increased iron may not be an etiological factor. Interestingly, PD medications may have differential associations with iron accumulation that need further investigation. © 2022 International Parkinson and Movement Disorder Society. Abstract : August Infographic : Dynamics of Nigral Iron Accumulation in Parkinson's Disease: From Diagnosis to Late Stage